A new species of Macropodus (Teleotsei: Osphronemidae) from Fujian Province, southern China - Chen, I-Shiung; Chiu, Yuh-Wen (Zootaxa, 2024)
A new Macropodus species was collected from the river basins of southeastern China. The new species Macropodus minnanensis, from Fujian Province, China can be well distinguished from congeners by the following combination of features: (1) dorsal fin with 13 spines and 7 soft rays; (2) anal fin with 20 spines and modally 10 soft rays; (3) vertical insertion of dorsal fin origin at second to third soft rays of anal fin; (4) longitudinal scale rows in midline modally 28; (5) transverse scale rows 14; (6) vertebrae 27 and (7) specific coloration: body with posteriorly black margin on scale pockets; eye greyish; a large opecular, deep black ocellus spot in male. The brief discussions of its related species are also provided.